Entry and Quality Choices in Child Care Markets - Paulo Bastos; Julian Cristia (Inter-American Development Bank (IDB), 2010)
Many developing countries have adopted the market approach for expanding the supply of child care, but little is known about the economic behavior of independent providers. This paper draws on uniquely rich administrative data on child care centers and their inputs from S\~ao Paulo to examine the role of local household income in shaping the entry and quality choices of private suppliers. It documents three main facts: (1) entry rates are considerably higher in high-income districts; (2) the quality of provision as measured by teachers schooling, group size and equipment is highly heterogeneous across space and increases systematically with local household income; and (3) a considerable share of centers operates below recommended (but not regulated) quality standards, especially in low-income districts. These findings accord with a model in which heterogeneous providers optimally adjust the quality of care to the willingness to pay for quality of local consumers. Market-driven heterogeneity in the quality of provision across space is a key consideration for understanding the effect of regulations on the supply of child care.
Keywords: D12; I21; I28; L21; L26; L51; O15; 330; Child care markets; Entry; Product quality; Minimum quality standards